2016
DOI: 10.1007/s10518-016-9949-9
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of strong ground motion on near-fault rock outcrop for engineering purposes: the case of the city of Xanthi (northern Greece)

Abstract: We combine probabilistic and deterministic approaches in an attempt to tackle a challenging topic in engineering seismology, that of the prediction of strong ground motion in urban areas located close to active faults, with sparse modern seismicity. The case we study is the city of Xanthi in northern Greece and we generate bedrock synthetic time series to be used as input motions into site-specific site effect analysis. We re-assess the seismic hazard using the probabilistic method and then perform hazard deag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 57 publications
1
7
0
Order By: Relevance
“…The earthquakes investigated using COMPSYN include simulating the low-frequency ground-motions (≤1 Hz) of the 2011 Lorca Mw5.2 event in Spain (Moratto et al, 2017), the 2009 L'Aquila Mw6.1 event in Italy (Cirella et al, 2012), the 2003 Bam Mw6.3 event in Iran (Nickman and Eslamian, 2010), and the 2000 Western Tottori Mw6.7 event in Japan (Monelli and Mai, 2008). Roumelioti et al (2017) and Ameri et al (2008) used COMPSYN to simulate the low-frequency content of ground motions of the potentially dangerous faults near Xanthi and Thessaloniki in northern Greece, respectively. Fälth et al (2015) benchmarked synthetic ground motions computed in 3DEC with COMPSYN to confir m the compatibility of the two software tools for wave propagation.…”
Section: Background To Synthetic Ground Motion Modellingmentioning
confidence: 99%
See 1 more Smart Citation
“…The earthquakes investigated using COMPSYN include simulating the low-frequency ground-motions (≤1 Hz) of the 2011 Lorca Mw5.2 event in Spain (Moratto et al, 2017), the 2009 L'Aquila Mw6.1 event in Italy (Cirella et al, 2012), the 2003 Bam Mw6.3 event in Iran (Nickman and Eslamian, 2010), and the 2000 Western Tottori Mw6.7 event in Japan (Monelli and Mai, 2008). Roumelioti et al (2017) and Ameri et al (2008) used COMPSYN to simulate the low-frequency content of ground motions of the potentially dangerous faults near Xanthi and Thessaloniki in northern Greece, respectively. Fälth et al (2015) benchmarked synthetic ground motions computed in 3DEC with COMPSYN to confir m the compatibility of the two software tools for wave propagation.…”
Section: Background To Synthetic Ground Motion Modellingmentioning
confidence: 99%
“…The COMPSYN program has mainly been limited to the simulation of low frequencies. The highfrequency content of synthetic ground motions was computed with stochastic models (Ameri et al , 2008;Nickman and Eslamian, 2010;Roumelioti et al, 2017), or with Empirical Green Functions (Moratto et al, 2017). The arguments for not using COMPSYN for the high-frequency content of synthetic ground motions were its inefficiency above 3 Hz (Nickman and Eslamian, 2010) and the computational cost of the Green's functions (Mai and Beroza, 2003).…”
Section: Background To Synthetic Ground Motion Modellingmentioning
confidence: 99%
“…For the geometric attenuation the default geometric spreading was applied, which has been also shown to be appropriate for Greece [e.g. Roumelioti, 2004;Roumelioti et al, 2017;Kkallas et al, 2018;Giannaraki et al, 2019]. Moreover, the anelastic attenuation was constrained by a mean frequency-dependent quality factor, Q(f) = 100f 0.8 , proposed for the broader Aegean Sea by Hatzidimitriou (1993Hatzidimitriou ( , 1995.…”
Section: Stochastic Simulation Of Macroseismic Data and Strong Motion...mentioning
confidence: 99%
“…By analyzing the ground motions of the Nepal Mw7.8 earthquake, it was found that the energy of the velocity pulse is concentrated in a short period range of 4-8 s [29]. When analyzing the ground motion, Roumelioti considered that the signal with a frequency below 3 Hz is a low-frequency signal and higher than 3 Hz is a high-frequency one [30]. Based on the above research, it can be found that the determination of frequency threshold is very complex.…”
Section: Pulse-like Ground Motions Identificationmentioning
confidence: 99%